Relação entre competências de gestão, adaptabilidade de carreira, e talento em profissionais que ocupam cargos de gestão - Nogueira, Carla Rossana de Araujo Torres (2020)
In the current market context, in which uncertainties have replaced the stability of work relationships, taking on management positions in organizations poses significant challenges for the construction of one's career (in addition to that of subordinates), given the nature of the activities carried out. Managers must: be at the forefront of processes, guide teams, in addition to meeting the implicit requirement of being a reference and model in technical requirements (knowledge and skills), as well as in the conditions of values and behaviors, to promote a greater competitive advantage for organizations through the development of their human resources. The general objective of the present study is to identify the competencies necessary to exercise management positions in Brazilian organizations, how to develop them and what are their relationships with the perceived talent and the career adaptability of the professionals. The specific objectives of this project are a) to present a critical analysis of the national scientific production on the skills necessary to exercise management positions; b) Investigate what skills are considered essential to the exercise of management positions by the professionals who occupy them, and how they developed these skills throughout their career; c) To characterize professionals who occupy management positions concerning the competencies considered necessary for the exercise of their work activities, talent levels, and career adaptability. For this, we adopted an observational and analytical design in a transversal cut through three stages. The first will consist of a theoretical study on management skills. The second will investigate, through a quantitative approach, the relationship between management skills, career adaptability, and the talent perceived in professionals who hold management positions in different regions of the country, and organizations of different sizes and segments. The third stage will investigate, through a qualitative approach, based on narratives about the construction of life, the competencies considered essential to the exercise of management positions by the professionals who occupy them, and how they developed these competencies throughout their career.